Soros Meets Students (Camera 2) - Part 1
Recording of George Soros in a public conversation with students on November 9, 2004 in the CEU Auditorium. Vice President for Student Services, Rositsa Bateson is moderating the discussion. First part contains George Soros' brief introductory remarks about the 2004 American elections and the opening of the floor for the question and answer session with CEU students. Topics covered: US elections, the war in Iraq, the current and future role of the Open Society Institute (OSI), regional issues of Central and Eastern Europe, the former Soviet Union and Central Asia, and Central European University itself.